Managing business process flows - Anupindi, Ravi. (Harlow : Pearson, 2014)
For graduate level courses in Operations Management or Business Processes. A structured, data-driven approach to understanding core operations management concepts. Anupindi shows how managers can design and manage process structure and process drivers to improve the performance of any business process. The third edition retains the general process view paradigm while providing a sharper, more streamlined presentation of the development of ideas in each chapter-all of which are illustrated with contemporary examples from practice.
Keywords: Production management -- Textbooks; Process control -- Textbooks